Methodological Aspects of Teaching Computer Modeling to Future Doctors (Journal of Educational Sciences, 2025)
The article discusses the integration of the disciplines of Anatomy and Computer Science into the educational process. The objective of the article is to describe a methodology for teaching computer modeling using augmented reality to improve the digital competence of future doctors. A questionnaire survey of 108 medical students was analyzed to assess their attitude toward computer modeling and a methodology was proposed that includes an elective course "Computer Modeling of Human Organs". A pedagogical experiment was conducted with the participation of 20 students, the results of which showed the high efficiency of the methodology, which is confirmed by the t-test for independent samples. Students rated the use of augmented reality in computer modeling of human organs as useful for learning the material. The methodology promotes the unification of knowledge from various disciplines, combining medicine and technology. The study confirms the effectiveness of an interdisciplinary approach that connects anatomy, medical imaging and digital technologies. Such integration stimulates the development of clinical thinking in students, encouraging them to actively analyze anatomical structures and engage in computer modeling.Keywords: Medicine, computer modeling, anatomy, education, visualization.